An Unusual Complication of Twin-to-Twin Transfusion Syndrome: Case of Intrauterine Limb Gangrene - Ali Khan, Md Owais; Richa, Richa; D S, Darshana; Mane, Shailaja (Journal of Neonatal Surgery, 2025)
Introduction: Twin-to-twin transfusion syndrome (TTTS) results from abnormal vascular anastomoses within the placenta, creating an imbalance in blood flow between the twins. TTTS only occurs in monozygotic twins with a monochorionic placenta. Twenty percent of all twin pregnancies are monochorionic, and TTTS affects up to 17% of monochorionic twins. The incidence of thrombosis in one of the twins is five percent. Case report: Here, we report a case of intrauterine limb gangrene secondary to TTTS. A preterm twins at 33 weeks of gestation were born to a second gravida mother. Antenatal ultrasonography showed monochorionic diamniotic placenta with polyhydramnios in one sac and oligohydramnios in the other. Twin A, which was the recipient twin, had a birth weight of 1.782 kg and was polycythemic (Hb- 26 gm/dl and HCT- 89%). Twin B, which was a donor twin, had a birth weight of 1.502 kg and was anemic(Hb- 9.0 gm/dl and HCT- 27%). Twin A, on examination, had bluish discoloration and absent peripheral pulses in the left upper limb( radial and ulnar arteries) and lower limb ( popliteal, posterior tibial, dorsalis pedis arteries). Ultrasound Doppler revealed a thrombus occluding the left radial, ulnar, and femoral artery). A partial exchange transfusion was done for Twin A and was started on low molecular weight Heparin. However, twin A had a stormy course and succumbed to disseminated intravascular coagulation and intraventricular hemorrhage. Twin B was transfused packed cells for anemia and was subsequently discharged. Discussion: Intrauterine thromboembolic phenomena, gangrene, and peripheral limb ischemia in the recipient twin are very rare complications of TTTS. Various causes of intrauterine gangrene have been described, the commonest being polycythemia leading to thrombosis in the recipient twin, which was evident in our case. Other causes include thromboembolic phenomenon due to thrombosis of placental vessels, as a complication of laser photocoagulation done antenatally, or as a result of umbilical artery steal syndrome. Conclusion: Antenatally diagnosed monochorionic twin gestation should be evaluated closely for TTTS and complications like heart failure, thromboembolic phenomena, and skin necrosis or ischemia. These complications can be prevented by in-utero interventions such as amnioreduction, fetoscopic laser photocoagulation, and septostomy..